Penggunaan Media Flanel Board dalam Mengembangkan Kemampuan Berbahasa Indonesia Anak Usia 5-6 Tahun di PAUD Az-Zakyyah Desa Kace - Qomariah, Nurul; Rahmah, Sri; Zetalianti, Zetalianti (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
In a learning activity, of course, requires a media so that children are more interested in participating in teaching and learning activities, the types of learning media that are often used in learning activities are very diverse. In PAUD, one of them is flannel board media. This study was conducted to find out about the use of flannel board media in developing Indonesian language skills for children aged 5-6 years. This research is a qualitative descriptive study, which provides a report on research results by describing and explaining the data obtained in the field regarding the use of flannel board media in developing Indonesian language skills in children. The results showed that the use of flannel board media was carried out through several stages, namely the planning stage, the implementation stage, and the assessment stage. The development of children's Indonesian language skills through flannel board media is considered to be able to improve children's Indonesian language skills, which is marked by increasing children's ability to understand Indonesian, express Indonesian language skills and literacy.